Răspuns :
ridici la patrat (atat in stanga cat si in dreapta) si devine:
(1-2*x)^2=(x+6)^2 < =>
<=>1+4*x^2-4*x =x^2+36+12*x <=>
<=>3*x^2-16*x-35=0
facem delta si avem : delta=b^2-4*a*c => delta=16^2+12*35=256+420=26^2
x1=(-b+rad(delta))/2*a=> x1=(16+26)/6 =7
x2=(-b-rad(delta))/2*a => x2=(16-26)/6=2/5
facand proba => ca doar x=7 este solutie.
(1-2*x)^2=(x+6)^2 < =>
<=>1+4*x^2-4*x =x^2+36+12*x <=>
<=>3*x^2-16*x-35=0
facem delta si avem : delta=b^2-4*a*c => delta=16^2+12*35=256+420=26^2
x1=(-b+rad(delta))/2*a=> x1=(16+26)/6 =7
x2=(-b-rad(delta))/2*a => x2=(16-26)/6=2/5
facand proba => ca doar x=7 este solutie.